EEG-MEG DIPOLE SOURCE LOCALIZATION OF N20 SOMATOSENSORY COMPONENT IN FRONTO-PARIETAL BRAIN TUMOR PATIENTS - MOHD NOOR, NOR SAFIRA ELAINA (2016)
The noise-normalized minimum-norm estimate (MNEs) approaches introduced in this study provides practical significance to improve the Magnetoencephalography (MEG) source localization for pre-surgical mapping of unclear anatomical landmark of the central sulcus (CS) due to tumor invading the primary somatosensory cortex, (SI) whereas the interhemispheric somatosensory parameter offers additional information to neurosurgeon as a potential quantitative measure of brain activities in the affected hemisphere. The primary cortical generator of N20m somatosensory evoked field (SEFs) originates from the tangentially oriented pyramidal neurons in the Brodmami's area 3b as demonstrated using equivalent current dipole (ECDs) analysis. However, changes in somatosensory cortical localization due to presence of tumor remain largely unknown using spatiotemporal estimates, dynamic statistical parametric maps (dSPM) and sLORETA approaches.